Considerations in Caring for Adult Patients in the Pediatric Intensive Care Unit - Needle, Jennifer Susan; Bjorklund, Ashley; Gupta, Sameer (Journal of Pediatric Intensive Care, 2017)
Pediatric providers are caring for a growing number of adults in pediatric in-patient settings due to the increasing survival of patients with historically pediatric disease. Beyond understanding the unique medical management of these patients, adult-specific ethical and legal issues must be considered. The aim of this article is to discuss four major issues unique to caring for adult patients: advance directives, confidentiality, decision-making capacity, and palliative care. To our knowledge, no literature exists focusing on the consideration of these specific concepts for the pediatric provider. An understanding of these issues in caring for adult patients in pediatric settings will enable pediatric practitioners to better consider patient autonomy, protect patient privacy, and ensure appropriate decision-making in critically ill patients.
Keywords: advance directive; Health Insurance Portability and Accountability Act; informed consent; Patient Self-Determination Act; patient preference; ethics; mental competency; decision-making capacity